2008
DOI: 10.1007/s10557-008-6091-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acarbose on Vascular Disease in Patients with Abnormal Glucose Tolerance

Abstract: Thus results so far available prove that acarbose is an effective and safe drug to treat abnormal glucose tolerance. They suggest that acarbose can help to control a broad spectrum of CV risk factors and may prevent CV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 54 publications
(59 reference statements)
0
32
0
1
Order By: Relevance
“…Improvement in postprandial hyperglycemia following treatment with an ␣-glucosidase inhibitor in patients with type 2 diabetes has been shown to have beneficial effects for cardiovascular disease (6,(8)(9)(10). Moreover, acarbose, an ␣-glucosidase inhibitor, delays progression of impaired glucose tolerance to diabetes and cardiovascular disease (7,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement in postprandial hyperglycemia following treatment with an ␣-glucosidase inhibitor in patients with type 2 diabetes has been shown to have beneficial effects for cardiovascular disease (6,(8)(9)(10). Moreover, acarbose, an ␣-glucosidase inhibitor, delays progression of impaired glucose tolerance to diabetes and cardiovascular disease (7,30).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of ␣ -glucosidase, which prevent the hydrolyzation of carbohydrates in the gastrointestinal tract, are commonly used to improve postprandial hyperglycemia in patients with type 2 diabetes and some have shown beneficial effects on both cardiovascular disease and progression to diabetes (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Due to it being scarcely digestible and generally having no detectable toxicity (Wehmeier and Piepersberg 2004), it is currently used in the therapy of type II diabetes, in which it can better control the blood sugar contents of patients after meals (Hanefeld et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…-Glucosidase inhibitors have been reported to treat postprandial hyperglycemia and hypertension, as well as to suppress the incidence of cardiovascular events 13 . In a previous study we showed that acarbose, an -glucosidase inhibitor, suppresses plasma levels of the remnant fraction in the fasting state 14 .…”
Section: Originalmentioning
confidence: 99%